The Influence of Knowledge, Attitude, and Family Supports on the Behavior of Utilization Garbage in Kendari City - Febriandi, Sarif; Kuswardinah, Asih; Raffy Rustiana, Eunike (Universitas Negeri Semarang, 2020)
Garbage was unused leftover goods. The middens in the city of Kendari in 2017 were 200 tons/day and in 2018 amounted 229.46 tons/day of unmanaged garbage around 10.29 tons/day. The purpose of this was to analyze the influence of knowledge, attitude, and family supports on the behavior of the utilization of garbage in Kendari city. This study was using cross sectional design. The sampling technique of this study were Stratified Random Sampling and purposive sampling techniques. The population in this study was all the people of Kendari city. Samples amounted to 400 respondents. The instrument was using questionnaire. Data were analyzed using univariate, bivariate with Chi square with a significance level of 5% (ÃŽÂ± = 0.05) and multivariate with logistic regression. The result of Chi square test showed that there was a significant relationship between knowledge (p=0.000; OR=2.481), attitudes (p=0.014; OR=1.829), family support (p=0.001; OR=2.398) on the behavior of the utilization garbage. The logistic regression results show that knowledge has the most influence on the behavior of garbage utilization. The society was expected to dispose of garbage in the place that has been provided and processing garbage.